Concise synthesis of tetrahydropyrans by a tandem oxa-Michael/Tsuji-Trost reaction - Wang, Liang; Li, Pengfei; Menche, Dirk (Angewandte Chemie. International edition, 2010)
A novel domino sequence facilitates the rapid assembly of polysubstituted tetrahydropyrans. The one-pot relay process generates up to three new stereogenic centers, including a tetrasubstituted carbon center, in a highly concise and convergent fashion from simple starting materials.